Seroprevalence of Human Parvovirus B19 Antibodies in Patients With Hemoglobinopathies in Basrah Province-Iraq - Kadhim Al Atbee, Mohaned A.; Al Hmudi, Hayder A.; Ali Al Salait, Sadeq K. (Scientific Journal of Medical Research, 2021)
Objectives: Human Parvovirus B19 infects human and cause no or mild disease, but more severe disease may occur in some people especially those with thalassemia and sickle cell anemia. In BV19 infections lead to suppression of the erythrocytes formation and acute erythroblastopenia often called transient aplasia crisis which may be life-threatening. The aim of this study was to detect the prevalence of Human parvovirus B19 antibodies in thalassemia and sickle cell patients in Basrah Province, Iraq. Methods: A 208 serum samples of both sexes with the age range 1 to 47 years’ old were collected from patients with haemoglobinopathies. All serum samples were performed by using ELISA kits. Results: Human parvovirus B19V IgG was detected in patient groups 186/208(89.4%), B19V IgM 20/208(9.6%) and B19V IgG 77/100(77%), B19V IgM 8/100(8%) of control groups. The studied patients were divided into 10 age groups, the age periods (1-5) and (10-15) were significantly prone to the infection (P less than 0.05). In contrast, the age period (46-50) years had significantly lower infection (P less than 0.05). Also, the patients were divided into 5 study groups. Conclusion: We concluded that high seroprevalence of anti-B19V IgG in thalassemia and sickle cell patients.